A Comparative study of financial performance of banking sector in Sri Lanka – An application of CAMEL rating system - Kobika, R. (Faculty of Management Studies & Commerce, University of Jaffna, 2018)
Purpose of this study is to compare the financial performance of state and private sector banks. The banking sector of developing countries is different from the developed countries. The banking sector of Sri Lanka plays a vital role in the Sri Lankan Economy specially commercial banks a re playing a major role in the banking sector of Sri Lanka. There are two types of commercials banks in Sri Lanka such as state and private commercial banks here the private commercial banks can be divided into domestic and foreign private commercial banks. The focus of this study is to compare the financial performance of state and private commercial banks using the Capital Adequacy, Assets Quality, Management Soundness, Earnings, Liquidity (CAMEL) rating system in Sri Lanka 2013-2017. Many studies are conducted in different countries to compare the financial performance of banking sector with the use of various statistical methods. In this study CAMEL rating system used to compare the financial performance of banks, it is one of the quantitative techniques and it is widely used in the current world. State banks should focus to increase their financial performance to compete and survive successfully in the current world and also private commercial banks try to achieve their target financial performance for their long survival.
Keywords: CAMEL; Financial Performance; Private Banks and State Banks; Rating System